Building a Tourism Village Ecosystem in Rawabogo Tourism Village Development - Indratno, Imam; Chamid, Chusharini; Judiantono, Tony; Syam, Husni; Al Zyanasya, Siti; Maharani, Vermanda S; Yuniar, Nurrishma; Zulfikar, Muhammad D (KnE Social Sciences, 2023)
Tourism plays a crucial role in community development and economic growth, contributing to income distribution, employment opportunities, and investment across various sectors. One form of tourism is village tourism, which serves as an alternative tourism option. However, Rawabogo Village, as a tourist village, has been unable to generate significant results and benefits for the environment and society. It requires a systematic effort to establish a tourism village ecosystem that can drive its development. The objective of this study is to construct a tourism village ecosystem for the development of Rawabogo Tourism Village. This involves examining the components of the tourism village ecosystem to determine the direction for its development, ensuring both economic and non-economic outcomes and benefits. The findings reveal that the current tourism village ecosystem in Rawabogo Village does not support its development adequately due to low community participation and a lack of tourism infrastructure. To address this, the first step is to implement community-based tourism development. This approach aims to encourage active community participation and engagement in managing and advancing Rawabogo Tourism Village. Additionally, future planning should prioritize the provision of necessary infrastructure and tourism facilities to support its growth and success. Keywords: tourism village ecosystem, tourism Village, Rawabogo Tourism Village